Synthesis and characterization of graphene oxide-based nanocomposite NaCr2O4 /GO for electrochemical applications - Naseem Akhtar (Elsevier, 2021)
This work reports the synthesis of NaCr2O4/GO nanocomposite using co-precipitation method for energy storage applications. Characterizations e.g., scanning electron microscopy (SEM) and X-ray diffraction (XRD) were performed to investigate the important optical and structural properties. The Crystalline size is seen to decrease from 28 nm for sodium chromite to 16.56 nm for nanocomposite NaCr2O4/GO. Raman results showed the existence of characteristic peaks for NaCr2O4/GO. Using cyclic voltammetry, the specific capacitance for NaCr2O4/GO was measured to be 455.5 F/g. The NaCr2O4/GO nanohybrids depicted significantly higher values of specific capacitance combined with extremely low charge transfer resistance, useful for various applications.